APPLICATION OF ANALYTIC REPRESENTATION OF DISTRIBUTION IN THE COMPLEX ANALYSIS - Rečkoski, Vasko; Manova Erakovikj, Vesna (Matematichki Bilten, 2008)
Our aim in this paper is to present how the analytic representation of distributions can be applied in some problems in the theory of complex analysis. In fact we give two theorems in this direction.